Yearbook of muslims in Europe. - Nielsen, Jørgen. (Yearbook of Muslims in Europe, 2011)
The Yearbook of Muslims in Europe provides an up-to-date account of the situation of Muslims in Europe. Covering 46 countries of Europe in its broader sense, the Yearbook consists of three sections: the first section presents a country-by-country summary of essential data with basic statistics and evaluations of their reliability, surveys of legal status and arrangements, organisations, et cetera Data have been brought up to date from the previous volume. The second section contains analysis and research articles on issues and themes of current relevance written by experts in the field. The final section provides reviews of recently published books of significance. The Yearbook is an important source of reference for government and NGO officials, journalists, and policy makers as well as scholars